2010
DOI: 10.3390/su2123777
|View full text |Cite
|
Sign up to set email alerts
|

National and International Standardization (International Organization for Standardization and European Committee for Standardization) Relevant for Sustainability in Construction

Abstract: Sustainability in construction has a short history in terms of principles, standardizations and applications. From the Brundtland Report “Our Common Future”, a new vision of the resource deficits, climate impacts and the social responsibility gave growth to the idea of sustainability also in design and construction. Consequently, in around 2000, the international and national organizations for standardization started to develop standards for the application of sustainable principles. This paper gives an overvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 1 publication
0
8
0
2
Order By: Relevance
“…By aligning their practices to national sustainable frameworks, construction stakeholders would be on track with sustainable construction practices (Tan et al , 2011). Construction project participants also move a step further by designing their sustainability policies and frameworks which guide their organizational efforts towards sustainability (Athapaththu et al , 2016; Krigsvoll et al , 2010; Elmualim et al , 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…By aligning their practices to national sustainable frameworks, construction stakeholders would be on track with sustainable construction practices (Tan et al , 2011). Construction project participants also move a step further by designing their sustainability policies and frameworks which guide their organizational efforts towards sustainability (Athapaththu et al , 2016; Krigsvoll et al , 2010; Elmualim et al , 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Baumgartner and Ebner (2010) further stated that sustainable construction practices may also depend on the industry, size of the company or other basic conditions. Krigsvoll et al (2010) stated that these practices reflect the context, preconditions and priorities and needs not only in the built environment but also in social infrastructure, as well as safe and healthy environments. Research studies conducted by Emmanuel (2004) and Mora (2007) on sustainable materials and Ugwu and Haupt’s (2007) study on sustainable indicators further confirmed the importance of a national, industry-specific approach to deliver sustainable construction.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, global scale standards by ISO and CEN, assessment tools and certification for sustainable building such as BREEAM, LEED, CASBEE, Passivhaus, Minérgie, Effinérgie, etc. are also being developed [4][5].…”
Section: Introductionmentioning
confidence: 99%